2007
DOI: 10.1182/blood-2007-05-093419
|View full text |Cite
|
Sign up to set email alerts
|

The HBS1L-MYB intergenic region on chromosome 6q23.3 influences erythrocyte, platelet, and monocyte counts in humans

Abstract: IntroductionHematologic variables that are routinely measured for clinical purposes are influenced by the individual genetic constitution of the patients 1,2 : in an ethnically homogenous population, we found that 62% of the variance in white blood cell counts, 57% of that in platelet counts, and 42% of the red cell count variance were due to genetic factors. 3 The identification of the underlying genes and sequence variants will not only help to explain the variability seen between patients, but should advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
76
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 17 publications
7
76
0
1
Order By: Relevance
“…9 In the present issue of Haematologica, the same group found that the JAK2 46/1 haplotype is associated with an increased frequency of acute myelomonocytic leukemia and a tendency to reduced survival because of death from infection in patients with NK-AML. 10 The latter findings need confirmation by other studies, for it is of great interest to establish whether the JAK2 46/1 haplotype is in fact a marker of myelomonocytic dysfunction and subsequently an unfavorable risk factor in NK-AML, as Nahajevszky et al suggest, and/or in other disease categories. 10 In fact, although the majority of studies have failed to detect any association of the 46/1 haplotype with hematologic and clinical parameters (Table 1), Tefferi et al found that the 46/1 haplotype status influenced survival in primary myelofibrosis, and evolution toward myelofibrosis in polycythemia vera.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…9 In the present issue of Haematologica, the same group found that the JAK2 46/1 haplotype is associated with an increased frequency of acute myelomonocytic leukemia and a tendency to reduced survival because of death from infection in patients with NK-AML. 10 The latter findings need confirmation by other studies, for it is of great interest to establish whether the JAK2 46/1 haplotype is in fact a marker of myelomonocytic dysfunction and subsequently an unfavorable risk factor in NK-AML, as Nahajevszky et al suggest, and/or in other disease categories. 10 In fact, although the majority of studies have failed to detect any association of the 46/1 haplotype with hematologic and clinical parameters (Table 1), Tefferi et al found that the 46/1 haplotype status influenced survival in primary myelofibrosis, and evolution toward myelofibrosis in polycythemia vera.…”
mentioning
confidence: 95%
“…10 The latter findings need confirmation by other studies, for it is of great interest to establish whether the JAK2 46/1 haplotype is in fact a marker of myelomonocytic dysfunction and subsequently an unfavorable risk factor in NK-AML, as Nahajevszky et al suggest, and/or in other disease categories. 10 In fact, although the majority of studies have failed to detect any association of the 46/1 haplotype with hematologic and clinical parameters (Table 1), Tefferi et al found that the 46/1 haplotype status influenced survival in primary myelofibrosis, and evolution toward myelofibrosis in polycythemia vera. 5 Moreover, it has been reported that the frequency of the JAK2 46/1 haplotype is increased in the context of severe inflammation, for instance Crohn's disease.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Studies on erythroid progenitors in vitro have clearly shown that only HBS1L expression correlates with high F-cell alleles [36]. It is of interest to note that the HBS1L-MYB intergenic region on chromosome 6q23.3 influences not only F-cell frequency but also a series of hematological parameters, including erythrocyte, platelet, and monocyte counts in humans [37].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 99%